Ecotoxicological assessment of chemotherapeutic agents using toxicity tests with embryos of Mellita quinquiesperforata - Mello, Luiza Costa [UNESP]; da Fonseca, Taina Garcia [UNESP]; Denis Moledode de Souza, Abessa [UNESP] (Elsevier, 2020)
The consumption of anticancer agents has increased in the recent decades, and these substances may be present in sewage. Consequently, they may reach the environment when sanitation infrastructure is ineffective. This study evaluated the toxicity of three anticancer agents—Tamoxifen (TAM), Cisplatin (CisPt), and Cyclophosphamide (CP)—on the development of embryos of the sand-dollar Mellita quinquiesperforata. Adult individuals were collected in sandy beaches, and gametes were obtained. Freshly-fertilized eggs were exposed to increasing sets of concentrations of each compound, and the effective concentrations needed to cause a 50% effect in the organisms (EC50) were calculated. The three compounds were toxic, and their EC50 values were 16.78 ± 2.42 ng·L−1 (TAM), 27.20 ± 38.26 ng·L−1 (CisPt), and 101.82 ± 70.96 ng·L−1 (CP). There is no information on the environmental levels of these compounds in Brazil, but as they were already detected in ng·L−1 levels worldwide, it can be expected that these substances pose environmental risks to the marine biota.
Keywords: Chemotherapeutics; Echinoderms; Ecotoxicity; Marine pollution; Pharmaceuticals